Understanding Europe’s forest harvesting regimes - Suvanto, Susanne; Esquivel Muelbert, Adriane; Schelhaas, Mart-Jan; Astigarraga, Julen; Astrup, Rasmus; Cienciala, Emil; Fridman, Jonas; Henttonen, Helena; Kunstler, Georges; Kändler, Gerald; König, Louis; Ruiz-Benito, Paloma; et al. (American geophysical union, 2025)
European forests are being shaped by active human use and management, and by harvesting of wood in particular. Yet, our understanding of how forests are harvested across Europe is limited, as the real harvest regimes are not well described by currently available data. Here, we analyse recent harvests, as observed in permanent plots of forest inventories in 11 European countries, totaling to 182,649 plots and covering all major forest types. We (a) characterize harvest regimes through the frequency and intensity of harvest events spatially across Europe, and (b) build models for the probability and intensity of harvest events at the plot-level and examine the links to potential drivers of harvest, including the pre-harvest forest structure and composition, climatic, topographic and socio-economic factors, and past natural disturbances. The results revealed notable variation in harvest regimes across Europe, ranging from high-frequency and low-intensity harvests in eastern Central Europe to low-frequency and high-intensity harvests in the north, with different strategies emerging in regions with similar total harvest rates. The harvest regimes were strongly driven by country-level variation, emphasizing the role of national-level factors. Pre-harvest forest properties were important drivers for the intensity of harvest, whereas the probability of harvest was more related to socio-economic factors and natural disturbances. The presented quantification of the forest harvesting regimes provides much needed detail in our understanding of the contemporary forest management practices in Europe, providing a baseline against which to assess future changes in management and strengthening the knowledge-base for decision-making on European level.
Keywords: forest management; forest harvesting